The Farallon Basin Basement Structure, South California Gulf by Interpretation of Potential and Seismic Data - Bartens (Peru), MSC, Lieutenant Marco (The International Hydrographic Review, 2015)
The Gulf of California is an active continental rift with an oblique and dextral opening displacement and is one of the few examples of an initiating continental rift where processes can be studied along a complete rift. Establishing the boundary between continental and oceanic basement holds the key to fully understanding the tectonic mechanisms acting on this initial rifting stage. Unfortunately, this is also a challenging task due to the presence of a newly formed oceanic crust. The aim of this work is to identify, delineate and estimate the thickness of the oceanic and continental crusts in the Farallon Basin. For this purpose, high-resolution 2D multichannel seismic reflection data from the Ulloa’s 2006 expedition along with gravity anomaly data from the global marine gravity database, obtained by repositioned radar altimetry from Geosat and ERS-1 satellites, was used. To assist with the interpre-tation, two-dimensional gravity modeling was carried out along each seismic profile, followed by 3D inversion of potential field data from the Farallon Basin area as constrained by the interpreted seismic profiles. The interpreted depths from the gravity models indicate that a thin oceanic crust exists at the center of the basin, with minimum thicknesses of 2.5 km in the abandoned south axis and 3 km in the dorsal axis. The continental crust gradually thickens towards the continent.